Reflexões marxistas enquanto aporte teórico para pensar o ensino de filosofia no contexto da educação integrada: um estudo de caso no IFPA-campus Belém - Damasceno, Cristiane Alves Pereira (2023)
Bearing in mind that our objective, in this research, is to analyze the division of labor, following the paths of book I, Capital, namely, chapters XI, XII and XIII – Cooperation, Division of labor, Manufacturing, Machinery and Large Industry – item 3. Immediate effects of mechanized production on the worker, in the light of Karl Marx and other authors with Marxist theoretical positions, whose relevant contributions make it possible to understand the antagonistic relationship between the economically predominant bourgeois class and the working class, which only has labor power as the only exchange good to maintain its survial, research on Marxist reflections as a theoretical contribution to thinking about the teaching of philosophy in the context of integrated education: a case study at IFPA – Campos Belém, in order to reflect on the teaching of philosophy in the context of integrated education, as a case study at IFPA – Campos Belém, for the contribution of the Marxist conception. For that, it is necessary. Present work as an educational principle from the perspective of omnilateral and unilateral education. Understand the division of labor and its consequences in manufacturing and the factory in Karl Marx, Explain the reverberations of the division of labor on the teaching of philosophy at IFPA – Campus Belém. Research is then carried out, our focus is on the qualitative nature of the case study, through the researcher's documentary, empirical observation and from there we outline interpretations that are close to the samples extracted from reality. In view of this, it appears that in the first result we see that unilateral education represents a unilaterality arising from the division of labor. The second result, we observe that as an ally of unilateral ideology, together with the economic cuts of neoliberalism, it aligned professional education during the period of the military dictatorship. This alignment caused a rupture in the teaching of philosophy, as a theoretical contribution, it was banned from school curricula, as a result, technical teaching predominated in the training of young people from the working class. In our third result we realize that integral training postulated by Karl Marx and the unitarist school and the teaching of philosophy are included in the PPC of Buildings, which imposes the observation that we obtained an answer to our research problem What is the reverberation of the Division of Labor on the Teaching of Philosophy, at IFPA – Campus Belém, with a contribution from the Marxist conception.